Financial payoff and records of the use of inland waterways as well as locks and slipways in Poland - Karczewska, Wiktoria; Gotowski, Rafał (Journal of Education, Health and Sport, 2021)
The basic deed regulating the use of inland waterways as well as locks and slipways in Poland is the water law. Fees for the use of inland waterways and their sections and water devices owned by the Treasury, located on inland surface waters, hereinafter "receivables", bear for: transport of passengers with assenger and cruise ships; transport of goods by cargo ships; sailing empty cargo ships; towing or floating of wood; use of locks and slipways. The minister competent for water management in consultation with the minister competent for inland navigationby way of regulation: defines inland waterways and their sections, and assigns these waterways and their sections to the appropriate regional water management boards of Polish Water; defines the unit rates of receivable for: sailing empty cargo ships; sailing of passenger and cruise ships; transport of goods by cargo ships and towing or floating of wood for use of locks and slipways.